Geo-Congress 2020. Selected papers from sessions of Geo-Congress 2020 : February 25-28, 2020, Minneapolis, Minnesota - Hambleton, James P.; Makhnenko, Roman; Budge, Aaron S. 1974- (American Society of Civil Engineers, 2020)
Selected papers from sessions of Geo-Congress 2020, held in Minneapolis, Minnesota, February 25-28, 2020. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 48 peer-reviewed papers on geoenvironmental engineering and sustainability. Topics include: geo-systems; geo-structural engineering; scour-soil transport; and unsaturated soil mechanics. GSP 319 will be of interest to practitioners and researchers developing sustainable practices in geotechnical engineering.
Keywords: Geotechnical engineering -- Congresses.; Sustainable engineering -- Congresses.; elektronické knihy; electronic books